Informal Fee Elimination and Student Performance: Evidence from The Gambia - Leanne Giordono; Todd Pugatch (Institute for the Study of Labor (IZA), 2015)
Informal school fees – for uniforms, books, and other supplies – are substantial in developing countries, often several times formal tuition. We evaluate a scholarship program that alleviated informal fees for girls in a subset of Gambian secondary schools. The program is unique because it overlapped with a government policy that had already eliminated formal school fees for girls, allowing for a comparison between program recipients and students who paid no tuition fees but were responsible for other expenses. We analyze the program using difference-in-differences, an identification strategy we support by documenting common pre-treatment outcome trends between treated and untreated schools. We find that informal fee alleviation increased female enrollment by 13% and the share of enrolled students who took the 9th grade exit exam by 11 percentage points. These results highlight the importance of informal fees in secondary school outcomes, even in settings where formal fees have been lifted.
Keywords: O15; I21; I25; 330; school fee elimination; informal fees; secondary school; gender gap; Gambia